(untitled) (Revista Contexto & Educação, 2026)
Prior conceptions refer to the understandings that students hold before receiving formal education on a given topic. Thus, this qualitative study sought to investigate the prior conceptions of students enrolled in a Biological Sciences undergraduate program regarding assessment. The research was conducted with 19 second-year students from a university located in the northwest region of Paraná, Brazil. As a data collection instrument, a questionnaire containing two open-ended questions was administered and answered individually. The content analysis aimed to understand the meanings attributed by the students to the assessment process, contributing to teacher education and the improvement of pedagogical practices. The results indicated that the preservice teachers hold diverse prior conceptions about assessment. Furthermore, studies such as this may assist higher education instructors in planning more effective teaching strategies, since the responses highlighted the importance of fostering more engaging and meaningful learning experiences aligned with students’ own perceptions and experiences, which should be valued.